Optimizing Local Functions In Drama Appreciation Materials - Agung Nugroho; Syukri Hamzah; Sarwit Sarwono; Agus Triyogo (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
This study aims to (1) Know the module development process Appreciation of local wisdom-based Drama Students of Indonesian language study program UNPARI Lubuklinggau (2) Module Appreciation Drama based on local wisdom Students of Indonesian language study program Lubuklinggau UNPARI are valid, practical, and effective. The method used is Research and Development (R & D) research and used the Dick & Carey model which is limited to 8 stages. The study produced new products in the form of a local wisdom-based Drama Appreciation module and tested valid, practical, and effective. Based on the results of the study it was known that validity was 81.25%, and practicality was known from small, medium and large tests. While the effectiveness of teaching materials is known as 6 people 30% get very good grades (A) with a score of 80-100, as many as 9 people 45% get 66-79 with a good category (B), the number of students who get enough grades (C) 1 person 5% with a score of 58, and students who scored less (D) as many as 4 people 20% with a value range of 46-55. based on the results of the study it can be concluded that the teaching material of the local wisdom-based Drama Appreciation course is valid, practical and effective for students of the Study Program. Indonesian language and literature education STKIP PGRI Lubuklinggau.